The Impact of Qualitative Characteristics of Accounting Information on The Effectiveness of Internal Control System Components: A Field Study in Insurance Companies Operating in The Republic of Yemen - Abdullah Hassan Al-Raimi Al-Manhouri; Ali Mahdi Lutf Al-Aqdhari (University of Science and Technology, Sana’a, Yemen, 2026)
The study aimed to identify and measure the impact of the qualitative characteristics of accounting information on the effectiveness of the internal control system, a field study in insurance companies operating in the Republic of Yemen. The study used a questionnaire to collect data from the community consisting of (11) insurance companies operating in the Republic of Yemen using a comprehensive inventory method. The number of valid questionnaires for analysis was (163). Simple and multiple regression analysis was used to test the hypotheses. The results of the field study showed a positive impact of the qualitative characteristics of accounting information (relevance, truthfulness of expression (reliability), verifiability, and comparability) on the effectiveness of the internal control system. The source of the positive impact was largely due to the comparability characteristic, followed by the relevance characteristic, then the verifiability characteristic, and finally the truthfulness of expression characteristic (reliability).The results of the field study revealed that the follow-up is ranked the lowest among the dimensions of the effectiveness of the internal control system, and reliability is ranked the lowest among the dimensions of the qualitative characteristics of accounting information. The study recommends that insurance companies should pay attention to the effectiveness of their internal control systems by conducting periodic reviews of the system and focusing on monitoring and follow-up to ensure the detection of potential risks and distortions.